The Effect of Animated Film Media on Early Childhood’s Ability to Recognize Mathematical Concepts Based on Gender (Animated Film Media for Education) - Yuni Nuraeni Setiana; Rustono Rustono; Eko Handoyo; Tri Suminar (International Conference on Science, Education, and Technology, 2021)
The goals of this study was to analyze differences in the effect of animated films, the impact of gender, the impact of animated movie and gender on the ability of early childhood to recognize mathematical concepts in material. This type of research is quantitative with a quasi-factorial (2x2) experimental design. The sampling technique was purposive sampling from 105 children aged 5-6 years in the Merpati PAUD group, Pati. The data was collected through the results of observations, documentation and tests. The data analysis technique used two-way ANOVA. The results showed F=17,545 with sig. 0.001 which means there is a difference effect of animated filmson children’s ability. Gender also affected kids’s ability beause the result F=5.399 with sig. 0.022 and for the combination of animated ilm media and gender, there was no significant effect on the ability to recognize mathematical concepts in preschool children with F=0.130 and significant value of 0.719. The conclusion showed that animated film media can be used to introduce mathematical concepts to early childhood.